The Impact of Audit Committees on the Quality of Financial Reporting: A Study on Saudi Companies - Alqahtani, Nada Abdullah; Al Barrak, Thamir Saad (The Arab Journal of Administration, 2025)
The quality of financial reports is one of the topics that has raised the interest of many academics and professionals in the importance of the financial and non-financial information they provide that meets the needs of the beneficiaries. This research was therefore aimed at examining the impact of the audit committee’s characteristics: (Independence, financial experience, total equity ownership, Commission size, number of meetings, total compensation, members’ tenure) On the quality of financial reports using the (Ohlson,1995) model, to achieve the research objectives, the quantitative approach was based on its suitability for the nature of the research. Many hypotheses were developed and statistically tested. Data were collected manually from the annual reports of Saudi non-financial companies during the period (2019-2016). The research results showed that the ownership of equity audit committee members and the total compensation were characteristics that had an important impact on the quality of financial reports. s compensation policy, taking into account a ceiling commensurate with the Commission’s role and without affecting its independence, Continuous follow-up by the CMA to verify companies’ commitment to implement the governance regulation in relation to the work of audit committees as this contributes to improving the quality of financial reports.